Integrando injeção de falhas e testes formais na validação da tolerância a falhas - Martins, Eliane (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1995)
This paper presents a test approach which integrates fault injection and formal testing. Fault injection is an experimental technique in which a system is validated in presence of special inputs: the faults. The term formal testing is used here to designate a functional test based on a formal specification of the system. This allow the selection of test inputs, i.e., faults and activations (inputs that activate system funcionalitics), to be based on this formal specification. The approach is centered on the realization of statistical testing. One important aspect of this type of test concems test size assessment: how many inputs are necessary to achieve validation objectives ? This is the main focus of the study presented here.